Beyond multiple mechanisms and a unique drug: Defective autophagy as pivotal player in cerebral cavernous malformation pathogenesis and implications for targeted therapies. Issue 1 (1st January 2016) - Marchi, Saverio; Trapani, Eliana; Corricelli, Mariangela; Goitre, Luca; Pinton, Paolo; Retta, Saverio Francesco
ABSTRACT: Cerebral Cavernous Malformation (CCM) is a major cerebrovascular disease of proven genetic origin affecting 0.3–0.5% of the general population. It is characterized by abnormally enlarged and leaky capillaries, which predispose to seizures, focal neurological deficits and intracerebral hemorrhage. Causative loss-of-function mutations have been identified in 3 genes, KRIT1 ( CCM1 ), CCM2 and PDCD10 ( CCM3 ). While providing new options for the development of pharmacological therapies, recent advances in knowledge of the functions of these genes have clearly indicated that they exert pleiotropic effects on several biological pathways. Recently, we found that defective autophagy is a common feature of loss-of-function mutations of the 3 known CCM genes, and underlies major phenotypic signatures of CCM disease, including endothelial-to-mesenchymal transition and enhanced ROS production, suggesting a unifying pathogenetic mechanism and reconciling the distinct therapeutic approaches proposed so far. In this invited review, we discuss autophagy as a possible unifying mechanism in CCM disease pathogenesis, and new perspectives and avenues of research for disease prevention and treatment, including novel potential drug repurposing and combination strategies, and identification of genetic risk factors as basis for development of personalized medicine approaches.